Konsep Sufisme ‘Shakhs-i Manevi dan Hizmet’ Muhammad Fethullah Gülen - Sulaiman Al-Kumayi (Universitas Islam Negeri Mataram, 2013)
This article examines the concept of shakh-i manevi and hizmet that are introduced by contemporary Turk Sufi ulama Muhammad Fethullah Gulen. Through this concept, Gulen attempts to encourage personal spirituality to transform gradually into collective personality. By this he means that this process should involve relevant parts of sufi teaching and integrate them directly into a community. This effort envisions a prototype of idealized community that hizmet should uphold. In this community, the followers of his movement work hand in hand to offer social services to the people regardless of their backgrounds.